Aryl hydrocarbon receptor (AhR) and pregnane X receptor (PXR) play both distinct and common roles in the regulation of colon homeostasis and intestinal carcinogenesis - Vázquez-Gómez, Gerardo; Petráš, Jiří; Dvořák, Zdeněk; Vondráček, Jan (Biochemical pharmacology, 2023)
Both aryl hydrocarbon receptor (AhR) and pregnane X receptor (PXR) belong among key regulators of xenobiotic metabolism in the intestinal tissue. AhR in particular is activated by a wide range of environmental and dietary carcinogens. The data accumulated over the last two decades suggest that both of these transcriptional regulators play a much wider role in the maintenance of gut homeostasis, and that both transcription factors may affect processes linked with intestinal tumorigenesis. Intestinal epithelium is continuously exposed to a wide range of AhR, PXR and dual AhR/PXR ligands formed by intestinal microbiota or originating from diet. Current evidence suggests that specific ligands of both AhR and PXR can protect intestinal epithelium against inflammation and assist in the maintenance of epithelial barrier integrity. AhR, and to a lesser extent also PXR, have been shown to play a protective role against inflammation-induced colon cancer, or, in mouse models employing overactivation of Wnt/β-catenin signaling. In contrast, other evidence suggests that both receptors may contribute to modulation of transformed colon cell behavior, with a potential to promote cancer progression and/or chemoresistance. The review focuses on both overlapping and separate roles of the two receptors in these processes, and on possible implications of their activity within the context of intestinal tissue.
Keywords: steroidní receptory; Intestine; Inflammation; Colon cancer; Pregnane X receptor; Aryl hydrocarbon receptor; zánět; Receptors, Aryl Hydrocarbon; Epithelial barrier; Receptors, Steroid; Carcinogenesis; Mice; Colon; zvířata; kolon; pregnanový X receptor; myši; Dietary contaminants; Pregnane X Receptor; receptory aromatických uhlovodíků; karcinogeneze; Microbial agonists; Animals